OsCBL1 modulates rice nitrogen use efficiency via negative regulation of OsNRT2.2 by OsCCA1 - Zhao Hu; Yutan Guo; Suping Ying; Yunting Tang; Jiawei Niu; Ting Wang; Ruifeng Huang; Hongwei Xie; Wenya Wang; Xiaojue Peng (BMC Plant Biology, 2023)
Abstract Background For cereal crop breeding, it is meaningful to improve utilization efficiency (NUE) under low nitrogen (LN) levels while maintaining crop yield. OsCBL1-knockdown (OsCBL1-KD) plants exhibited increased nitrogen accumulation and NUE in the field of low N level. Results OsCBL1-knockdown (OsCBL1-KD) in rice increased the expression of a nitrate transporter gene OsNRT2.2. In addition, the expression of OsNRT2.2, was suppressed by OsCCA1, a negative regulator, which could directly bind to the MYB-binding elements (EE) in the region of OsNRT2.2 promoter. The OsCCA1 expression was found to be down-regulated in OsCBL1-KD plants. At the low Nitrogen (N) level field, the OsCBL1-KD plants exhibited a substantial accumulation of content and higher NUE, and their actual biomass remained approximately as the same as that of the wild type. Conclusion These results indicated that down-regulation of OsCBL1 expression could upregulate the expression of OsNRT2.2 by suppressing the expression of OsCCA1and then increasing the NUE of OsCBL1-KD plants under low nitrogen availability.